Deteksi Turnip Mosaic Virus (TuMV) pada Tanaman Brokoli di Boyolali, Indonesia: Deteksi Turnip Mosaic Virus (TuMV) pada Tanaman Brokoli di Boyolali, Indonesia - Probowati, Wiwit; Firyalunfah, Pilar Rosatria; Nabila, Tsania Taskia (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Turnip mosaic virus (TuMV) is one of the emerging viruses that causes serious yield losses of brassica vegetables, including Indonesia. Broccoli (Brassica oleracea var. italica) is a potential horticultural commodity in Indonesia because of its many benefits. The objective of this study was to detect TuMV-infecting broccoli using reverse transcription polymerase chain reaction (RT-PCR) technique. Field survey has been conducted to determine disease symptoms in broccoli field Boyolali, Central Java. This study was conducted through several phases, which are: leaves sample collection on the field, virus RNA isolation, RT-PCR, and TuMV detection using coat protein (CP) specific primer. The result of field observed broccoli plant with several symptom of TuMV infection, such as: mosaic symptom leaf, blister leaf, vein banding, vein clearing, and yellowing of leaf spot. The detection of TuMV by RT-PCR showed that broccoli with those symptoms observed is positively infected by TuMV. Specific DNA band was amplified from infected plant on 800 bp. This study is report of naturally infection of TuMV on broccoli with those symptoms at Boyolali, Central Java, Indonesia.